Penerapan Nilai-Nilai Profil Pelajar Pancasila melalui Pengenalan Kearifan Lokal Masyarakat Amfoang dalam Pembelajaran PKN - Nikson Kollo; Suyono Suyono; Ade Eka Anggraini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Civic Education (Civics) plays an important role in shaping students' character and national identity. This study aims to explore and explore the application of Pancasila student profile values through the introduction of local wisdom of the Amfoang community in Civics learning in elementary schools. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results showed that the Pancasila learner profile consists of six main dimensions, while the local wisdom of the Amfoang community includes values such as presenting betel nut and tobacco, using traditional blankets, collecting honey, and the tradition of oral invitations. There is a significant relevance between Amfoang's local wisdom values and the Pancasila learner profile, especially in the aspect of man's relationship with God. The integration of local wisdom values in Civics learning can improve students' understanding of Pancasila values, strengthen cultural identity, and shape students' inclusive and multicultural characters. This research provides guidance for teachers and education policy makers in developing learning approaches that are contextual and relevant to local realities to improve the effectiveness of civic education in Indonesia.